NOD2 Risk Variants and Pathological Bacterial Translocation in Decompensated Cirrhosis Reply - Harputluoglu, Murat M. M.; Bilgic, Yilmaz; Erdogan, Mehmet Ali; Atayan, Yahya; Cagin, Yasir Furkan; Dertli, Ramazan; Demirel, Ulvi (Springer, 2016)
[Abstract Not Available]
Keywords: Peritonitis